Concise formal synthesis of (-)-(6R,11R,14R)-colletallol via D-proline catalysed alpha-aminooxylation-Wittig olefination strategy - Dey, Soumen; Gadakh, Sunita; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2019)
An efficient enantioselective formal synthesis of marine macrolide (-)-(6R,11R,14R)-colletallol has been achieved starting from commercially available raw materials. The key reactions include the D-proline catalyzed a-aminooxylation of aldehyde followed by Horner-Wardsworth-Emmons olefination in a sequential fashion to give the macrolide key intermediate 5 in high enantiomeric purity (97% ee) and high overall yield (32%).
Keywords: alpha-aminoxylation; Asymmetric synthesis; Enantioselectivity; Natural products; organocatalysis